Enhancing Moral Literacy Through Structured Habitual Behavior Intervention: A Quasi-Experimental Study in Chinese Vocational Education School - Wang Daowang, Immanuel T San Diego (Journal of Daoist Studies, 2026)
Background: Moral literacy is essential for vocational students to navigate ethical challenges in personal and professional contexts. Conventional moral education often yields modest improvements, highlighting the need for structured interventions that cultivate ethical habits and actionable moral reasoning. Objective: This study examined the effects of habitual behavior cultivation on the moral literacy of vocational students, focusing on three dimensions: ethical sensitivity, ethical reasoning, and ethical motivation/action. Methods: A quasi-experimental design was employed involving 120 students from two intact classes at a higher vocational college in Guangdong Province. One class served as the experimental group, receiving structured interventions integrating classroom behavior routines, community service, and reflective exercises, while the control group continued with standard moral education practices. Moral literacy was assessed using a validated 24-item Likert scale grounded in Tuana’s Moral Literacy Framework. Pre-test and post-test data were collected over one semester. Multivariate Analysis of Covariance (MANCOVA) and univariate ANOVAs were performed to evaluate intervention effects. Results: Pre-test scores indicated comparable low levels of moral literacy across both groups. Post-intervention, the experimental group demonstrated substantial improvements, achieving high scores in ethical sensitivity (M = 4.05), reasoning (M = 4.01), and motivation/action (M = 3.91), whereas the control group showed moderate gains. Multivariate analyses (Pillai’s Trace) confirmed significant overall differences (p < .001), and univariate tests indicated large, statistically significant improvements for the experimental group across all dimensions. Conclusions: Structured habitual behavior interventions significantly enhance moral literacy in vocational students, exceeding the effects of conventional curricula. The findings suggest that integrating habit-based ethical activities, reflection, and real-world moral practice can effectively develop students’ ethical competence. Educational institutions are encouraged to adopt these strategies to promote sustained moral development, while future research should assess the long- term retention and cross-cultural applicability of such interventions.